Eksistensi Putusan Dewan Kehormatan Penyelenggara Pemilu (Dkpp) Terhadap Pelanggaran Kode Etik Ditinjau Dari Perspektif Kepastian Hukum - Erwin Syarif; Wandi; Ali Azhar (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
The decision of the Election Organizers Ethics Council (DKPP) regarding violations of the Code of Ethics, once made, has immediate legal force and direct legal consequences for the election organizers. The Bawaslu (Election Supervisory Board) is obligated to supervise the implementation of this decision, and legally, every decision made by DKPP must be executed by the concerned parties. The research questions in this study are as follows: 1. What is the philosophical and juridical foundation of the position of DKPP in enforcing violations of the election organizers' code of ethics? 2. How is the existence of the DKPP's decision in response to violations of the code of ethics viewed from the perspective of legal certainty?.The approach used in this research is a normative juridical method, which involves processing secondary data obtained from library studies such as official documents, books, and laws related to the research issues. The author uses theories and concepts of democratization, authority, and legal certainty. The results of the research and discussion indicate that the position of DKPP's decision, based on DKPP Regulation No. 1 of 2013 concerning the Code of Ethics Procedural Guidelines for Election Organizers, stipulates that the decision is